The Effect of Interpersonal Communication and School Leadership on the Performance of Junior High School Teachers in Kapuas Barat District of Kapuas Regency - Anwar Mikhaharahap; Misransyah Akos; Cici Asmawatiy; Riky Welly Saputra (East Asian Journal of Multidisciplinary Research, 2022)
The objectives to be achieved in this study are to determine and analyze: (1) The effect of interpersonal communication on the performance of junior high school teachers in West Kapuas District, Kapuas Regency and (2) The influence of the Principal's Leadership on the performance of Junior High School teachers in Kapuas District West of Kapuas Regency. The method used in this study is the explanatory method with multiple regression techniques, with 55 teachers from 10 schools in West Kapuas District as respondents. In this research, to test the hypothesis using the SPSS program tool with a multiple regression approach. The results showed that there was a positive and significant influence between interpersonal communication and teacher performance where the significance value of the results of this study was 0.000 which is smaller than the level of confidence used 0.05. Likewise, the influence of the principal's leadership on the performance of the teacher council shows a significant effect with a significant result of 0.004 and is smaller than the 0.05 confidence level.